Sonic hedgehog is required for the assembly and remodeling of branchial arch blood vessels - Kolesová, Hana; Roelink, Henk; Grim, Miloš (Developmental dynamics, 2008)
Sonic hedgehog (Shh) is a morphogen involved in many developmental processes. Injection of cells (5E1) that produce a Shh-blocking antibody causes an attenuation of the Shh response, and this causes vascular malformations and impaired remodeling characterized by hemorrhages and protrusions of the anterior cardinal vein and outflow tract, delayed fusion of the dorsal aortae, impaired branching of the internal carotid artery, and delayed remodeling of the aortic arches. Distribution of smooth muscle cells in the vessel wall is unchanged. In 5E1-injected embryos, we also observed impaired assembly of endothelial cells into vascular tubes, particularly in the sixth branchial arch, around the anterior cardinal vein and around the dorsal aorta. In 5E1-treated embryos, increased numbers of macrophage-like cells, apoptotic cells, and a decreased level of proliferation were observed in head mesenchyme. Together, these observations show that Shh signaling is required at multiple stages for proper vessel formation and remodeling.
Keywords: cévy; ptačí proteiny; proteiny hedgehog; hybridomy; Blood Vessels; In Situ Hybridization; branchiální krajina; hybridizace in situ; Hybridomas; financování organizované; Avian Proteins; Financing, Organized; zvířata; myši; Cells, Cultured; Immunohistochemistry; imunohistochemie; Mice; křepelky a křepelovití; Cell Transplantation; Gene Expression Regulation, Developmental; Hedgehog Proteins; Branchial Region; protilátky; kultivované buňky; transplantace buněk; Antibodies; vývojová regulace genové exprese; Animals; Quail